Enhancing Quality of Higher Education for Graduate Research Students Development - Abiddin, Norhasni Zainal; Ismail, Affero; Taniredja, Tukiran (EDUCARE, 2013)
ABSTRACT: Quality education becomes a major issue in higher education. The numbers of graduate students to pursue their higher education keep increasing by years. In the meantime, the institutions of higher learning are striving to attract more students, especially at the graduate level by making every effort to provide quality education. Graduate students contribute to the development of research outcome. Some scholars proposed that the strategic success of a service organization depends on its ability to consistently meet or exceed customer service expectations. A constant effort should be made to ensure the customer satisfaction. This paper provides the relevant input for effective resource development in institutional of higher education. The approach would address the needs of students further along the process with an emphasis on data gathering, management and analysis, compiling a thesis or dissertation, assessment, and the publishing of research results. Another approach would relate to generic aspects of graduate growth, development, and progress. Conceptual evidence is presented which combination of resource needs to focus. It is hoped to contribute a proper insight of effective resource in developing distinguished human capital.KEY WORDS: Higher education, quality education, graduate students, resource development, and student development.Â Â Â Â About the Authors: Assoc. Prof. Dr. Norhasni Zainal Abiddin is a Lecturer at the Department of Professional Development and Continuing Education, Faculty of Educational Studies UPM (Putra University of Malaysia), 43400 Serdang, Selangor, Malaysia; Affero Ismail is a Staff at the Manpower Department, Ministry of Human Resource, Federal Government Administration, 62530 Putrajaya, Malaysia; and Prof. Dr. Haji Tukiran Taniredja is a Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto) in Central Java, Indonesia. Corresponding author is nonie@putra.upm.edu.myHow to cite this article? Abiddin, Norhasni Zainal, Affero Ismail & Tukiran Taniredja. (2013). âEnhancing Quality of Higher Education for Graduate Research Students Developmentâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.133-146. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 19, 2012); Revised (January 30, 2013); and Published (February 17, 2013).Â  Â